The Mindset of Small-scale Garment Business: Production and Marketing Perspective - Muhardi, M; Oktini, Dede R.; Nurdin, N; Hami, Norsiah Binti; Omar, Salmah Binti; Shafie, Shafini binti Mohd (KnE Social Sciences, 2024)
This research was conducted to analyze the mindset of small-scale garment business actors from the perspectives of production and marketing, considering that these two aspects have an important role in creating added value in the value chain of small-scale garment businesses. This research uses a qualitative descriptive method. The type of data required is primary data obtained from in-depth interviews with actors from garment businesses located in Bandung City and Bandung Regency. The research results find that the mindset of small-scale garment entrepreneurs from a production perspective shows that most of them are oriented toward always looking for the best production methods and never feeling satisfied (creativity is not a methodology but a mindset). Given that the market for garment products wants to have a relatively fast product life cycle, the emergence of market responses to the products offered is an important input for garment businesses to produce market-oriented products. In relation to the production mindset, garment businesses pay attention to the marketing mindset, where customer loyalty is considered crucial since customers are valued as an asset that supports the business instead of a burden, and marketing is considered a margin center, not a cost center. Keywords: business, marketing, mindset, production, small-scale garment